Gene by environment interaction in asthma - Weiss, Scott (Henry Stewart Talks, 2007)
Interaction definition, Types of environmental exposures, G x E interaction: key issues and study designs, Potential methodologic issues, G x E interaction in linkage studies of asthma, ADRB2, GSTM1 and CD14 and smoking, TLR4 and endotoxin, Asthma pharmacogenetics, Advantages and disadvantages to studying G x E interactions
Archived at 2021/02/25